Diagnostic accuracy and differential associations between ratings of functioning and neuropsychological performance in non-Hispanic Black and White older adults. Issue 2 (17th February 2022) - Graves, Lisa V.; Edmonds, Emily C.; Thomas, Kelsey R.; Weigand, Alexandra J.; Cooper, Shanna; Stickel, Ariana M.; Zlatar, Zvinka Z.; Clark, Alexandra L.; Bondi, Mark W.
ABSTRACT: Objective We recently demonstrated that relative to consensus-based methods, actuarial methods may improve diagnostic accuracy across the continuum of cognitively normal (CN), mild cognitive impairment (MCI), and dementia in the overall National Alzheimer's Coordinating Center (NACC) cohort. However, the generalizability and comparative utility of current methods of diagnosing MCI and dementia due to Alzheimer's disease and related disorders (ADRD) are significantly understudied in non-Hispanic Black (NHB) older adults. Thus, we extended our previous investigation to more specifically explore the utility of consensus-based and actuarial diagnostic methods in NHB older adults.Method: We compared baseline consensus and actuarial diagnostic rates, and associations of ratings of functioning with neuropsychological performance and diagnostic outcomes, in NHB (n = 963) and non-Hispanic White (NHW; n = 4577) older adults in the NACC cohort.Results: 60.0% of the NHB subsample, versus 29.2% of the NHW subsample, included participants who met actuarial criteria for MCI despite being classified as CN or impaired-not-MCI per consensus. Additionally, associations between ratings of functioning and neuropsychological performance were less consistent in NHB participants than in NHW participants.Conclusions: Our results provide evidence of differential degrees of association between reported functioning and neuropsychological performance in NHB and NHW older adults, which may contribute to racial group differences in diagnostic rates, and prompt consideration of the strengths and weaknesses of consensus-based and actuarial diagnostic approaches in assessing neurocognitive functioning in NHB older adults.